Clinical training and practice of using digital health solutions among healthcare workers in clinical settings during Hajj season - Alghamdi, Saeed Mardy (Journal of the Pakistan Medical Association, 2024)
Digital health solutions are widely used in Saudi Arabia, but training, clinical practice and challenges related to using digital health applications have not been evaluated from the perspective of healthcare workers during the Haj season in Makkah. The current study was planned to explore clinical training, practices and challenges related to the use of digital health among healthcare workers during the Haj season from June to August 2023. Of the 470 subjects, 347(73.8%) were males and 123(26.2%) were females. The overall median age was 40 years (interquartile range: 27-56 years). In the clinical practice of using digital health, 185(39.4%) of the subjects strongly agreed that digital health was useful and beneficial during transportation difficulties, and 167(35.5%) strongly agreed that digital health applications had changed their working routine during the Haj season. Negative outcome expectations were the challenge least reported by 72(15.3%) respondents.